2015
DOI: 10.1186/s12885-015-1326-6
|View full text |Cite
|
Sign up to set email alerts
|

The emerging outcome of postoperative radiotherapy for stage IIIA(N2) non-small cell lung cancer patients: based on the three-dimensional conformal radiotherapy technique and institutional standard clinical target volume

Abstract: BackgroundThe aim of this study was to evaluate the clinical efficacy of postoperative radiotherapy (PORT), administered using three-dimensional conformal radiotherapy (3D-CRT) and our institutional standard clinical target volume (CTV) delineation, for completely resected stage IIIA(N2) non-small cell lung cancer (NSCLC).MethodsFrom 2005 to 2012, consecutive patients with pT1-3N2 NSCLC who were treated with PORT employing our institutional CTV delineation after complete surgery or who underwent complete resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 29 publications
2
30
0
1
Order By: Relevance
“…Recently, Feng et al . designed a patterns-of-failure study after R0 surgery in resected N2 disease to evaluate the rationale of the proposed PORT CTVs based on the most likely sites of nodal failure, and the institutional standard CTV delineation for PORT was developed in their hospital [ 29 30 ]. Similar to these studies, our CTV encompassed the bronchial stump and involved mediastinal nodal stations and their next draining stations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Feng et al . designed a patterns-of-failure study after R0 surgery in resected N2 disease to evaluate the rationale of the proposed PORT CTVs based on the most likely sites of nodal failure, and the institutional standard CTV delineation for PORT was developed in their hospital [ 29 30 ]. Similar to these studies, our CTV encompassed the bronchial stump and involved mediastinal nodal stations and their next draining stations.…”
Section: Discussionmentioning
confidence: 99%
“… 23 26 Feng et al have demonstrated that PORT was an independent prognostic factor for improved locoreginal free Survival (HR=0.2, 95% CI 0.1–0.5; P =0.001) and improved OS (HR=0.4, 95% CI 0.2–0.7; P =0.001). 27 The Lung Adjuvant Radiotherapy Trial (LungART, NCT00410683), a randomized trial of modern PORT vs no PORT in patients with resected NSCLC, is ongoing. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Feng et al showed that PORT was an independent prognostic factor for improved OS (HR=0.4, 95% CI 0.2–0.7; P =0.001); female sex (HR=0.5, 95% CI 0.3–0.7; P <0.001) and LNR>20% (HR=2.4, 95% CI 1.7–3.3; P <0.001) were the other factors for OS. 27 Wang et al demonstrated that in stage IIIA-pN2 NSCLC, the use of PORT demonstrated better survival results than no PORT for patients with positive LNs with n>3, but not for patients with positive LNs with n≤3. 17 Other studies have reported that several clinical and pathological factors, such as the number of pathologically involved lymph node stations, 32 , 33 extracapsular extension, 34 lymph node skip status and positive LNR 12 16 should be considered when evaluating the risks and benefits of PORT.…”
Section: Discussionmentioning
confidence: 99%
“…3,24 Nonetheless, the rate of distant failure remained high (66.7%), consistent with that in other studies. 3,13,25,26 There is an association between pN2 disease and distant failure.…”
Section: Discussionmentioning
confidence: 99%